Cerebral Networks Linked to Itch-related Sensations Induced by Histamine and Capsaicin - Vierow, Verena; Forster, Clemens; Vogelgsang, Rebekka; Dörfler, Arnd; Handwerker, Hermann Otto (Acta Dermato-Venereologica, 2015)
This functional magnetic resonance imaging (fMRI) study explored the central nervous processing of itch induced by histamine and capsaicin, delivered via inactivated cowhage spicules, and the influence of low-dose naltrexone. Scratch bouts were delivered at regular intervals after spicule insertion in order temporarily to suppress the itch. At the end of each trial the subjects rated their itch and scratch-related sensations. Stepwise multiple regression analyses were employed for identifying cerebral networks contributing to the intensities of "itching", "burning", "stinging", "pricking" and "itch relief by scratching". In the capsaicin experiments a network for "burning" was identified, which included the posterior insula, caudate and putamen. In the histamine experiments networks for "itching" and "itch relief" were found, which included operculum, hippocampus and amygdala. Naltrexone generally reduced fMRI activation and the correlations between fMRI signal and ratings. Furthermore, scratching was significantly less pleasant under naltrexone.
EVALuna2:2447

HealthRec - Empfehlungssystem zur Behandlung des metabolischen Syndroms im Smart Home - Bauer, Jochen; Michl, Markus; Kettschau, Anna-Katharina; Wiebe, Sergej; Vierow, Verena; Ge, Mouzhi; Franke, Jörg (Zukunft Lebensräume - Gesundheit, Selbstständigkeit und Komfort im demografischen Wandel Konzepte und Technologien für die Wohnungs-, Immobilien-, Gesundheits- und Pflegewirtschaft, 2016)